REASON OF INCREASING CASES OF MARRIAGE DISPENSATION AGAINST WOMEN'S RIGHTS - Nailur Rahmi; Elimartati Elimartati (AGENDA: Jurnal Analisis Gender dan Agama, 2021)
The purposes of this study are to find out and to analyze causes of the increasing cases of marital dispensation on women’s right. Field research with normative juridical research are used. It was done by examining several decisions on marital dispensation cases at Batusangkar Religious Court. Data source are derived from the ones who conducted marital dispensation during interview session, and secondary data are from various literature review such as related books and journals. The results reflect causes of the increasing cases of marital dispensation is promiscuity, adultery, already having children, economic factors and poverty. The causes of the increasing cases of marital dispensation has an impact on the rights of women in the reproductive sector, because they are married at a young age. Therefore, the marriage dispensation regulation needs to be reviewed because it has not caused a deterrent effect by imposing sanctions on the person who conducted marital dispensation.